Out-of-pocket expenditure on maternal health care in two backward districts of Karnataka: A cross-sectional study - Shivakumar Swamy; Jyothi S Lakshmi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Maternal health is an important indicator of a woman's health and society. Safe motherhood is still a nightmare in many communities. Medical services related to maternal health are almost free in India, yet many families face significant out-of-pocket (OOP) expenditure, especially in poor communities in the rural areas, leading to more poverty and exclusion. This study has the aim of revealing OOP expenditure on maternal health care in rural areas. METHODS: A community-based cross-sectional study was conducted among 386 randomly selected mothers who had delivered a baby in the past 2 years in two backward districts of Karnataka using a mixed method. Univariate, bivariate, and t-tests were used for the analysis. RESULTS: The findings revealed that poor education and low income have a significant association with OOP expenditure. Getting laboratory services, purchasing medicine from the market, informal payments to the hospital staff, and other indirect costs are the major components of catastrophic expenditure for the poor mothers. CONCLUSION: It is concluded that there is strong evidence to support the high burden of maternal health-care spending. More comprehensive schemes are needed in the government's maternal health-care services to reduce out-of-pocket expenses.